Overinvestment and Environmental, Social, and Governance (ESG) Performance - Alis Akbar (Journal of Applied Accounting and Taxation, 2024)
This study aims to examine the effect of overinvestment on environmental, social, and governance (ESG) performance. The purpose of this study, the formulation of the problem in this study is whether overinvestment affects environmental, social, and governance (ESG) performance. This study used Descriptive Statistical analysis, Linear Regression Analysis, and a Hypothesis Test consisting of a t-test, F Test, and R Square (Determination Coefficient). The population used in this study was a group of manufacturing companies listed on the Indonesia Stock Exchange (IDX), but only 29 companies were sampled in this study. Data is taken from 2020-2023. As a result, overinvestment, board size, ROA, and leverage significantly negatively affect ESG performance. However, sales growth has a significant positive effect on ESG performance. The real implication of this research is that it can be used as a consideration for companies in making decisions to improve corporate social responsibility so that companies with good ESG performance can be used as a review tool for investors in investing.